2020
DOI: 10.3390/polym12081716
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Microbial Resistance of Resin-Based Dental Sealant by Sulfobetaine Methacrylate Incorporation

Abstract: Prevention of dental caries is a key research area, and improvement of the pit and fissure sealants used for caries prevention has been of particular interest. This report describes results of incorporating a zwitterion, sulfobetaine methacrylate (SB), into photo-polymerized resin-based sealants to enhance resistance to cariogenic bacteria and protein adhesion. Varying amounts (1.5–5 wt%) of SB were incorporated into a resin-based sealant, and the flexural strength, wettability, depth of cure, protein adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…It has been previously demonstrated that the incorporation of zwitterions in resin-like materials results in the copolymerization and immobilization of zwitterions [ 38 ], resulting in a stable form of the material. The results presented here are in agreement with those of previous studies, wherein no significant changes were observed with zwitterion-containing polymers in terms of both the protein-repellent and the physical/mechanical properties [ 17 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been previously demonstrated that the incorporation of zwitterions in resin-like materials results in the copolymerization and immobilization of zwitterions [ 38 ], resulting in a stable form of the material. The results presented here are in agreement with those of previous studies, wherein no significant changes were observed with zwitterion-containing polymers in terms of both the protein-repellent and the physical/mechanical properties [ 17 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of MPC and SB in this study was based on previous studies, which examined different concentrations of MPC and SB. In those studies, more than 5 wt% of the zwitterion resulted in the deterioration of the mechanical properties, while less than 3 wt% led to less effective protein-repellent properties and biofilm resistance [ 15 , 16 , 17 , 28 ]. Despite a small decline, the mechanical properties obtained in this study are adequate in terms of the minimum required values stated in International Standard ISO 20795-2 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported on the antibacterial properties of phenolic compounds, such as polyphenol and flavonoids, against C. albicans [ 12 , 25 ]. The antioxidant activity and effect of the phenolic component of CO were confirmed by previous studies, along with its antibacterial activity against Streptococcus mutans and C. albicans , which are two major oral pathogens [ 21 , 26 ]. Previous studies have demonstrated that CO were established, as well as secondary metabolites, such as phenolic, flavonoid, phthalide, and 3-butylidenephthalide synthesis.…”
Section: Resultssupporting
confidence: 62%
“…Flowable resin composites have been clinically proven to be an effective dental treatment over the last 60 years are a popular restorative material in dentistry because of the good flowability and color, which is similar to that of natural tooth enamel [ 1 , 2 ]. Flowable resin composites have a diverse variety of applications, including preventive resin restoration, pit and fissure sealing, restoration repair, and cavity lining [ 3 ]. Although flowable composite resins have shown long-term clinical success, they tend to accumulate more bacteria and dental plaque than enamel and other restorative materials [ 4 ].…”
Section: Introductionmentioning
confidence: 99%